From Practice to Publication: The Promise of Writing Workshops. Issue 1 (November 2022) - Lavinghouze, S. René; Kettel Khan, Laura; Auld, M. Elaine; Sammons Hackett, Doreleena; Brittain, Danielle R.; Brown, David R.; Greaney, Eryn; Harris, Diane M.; Maynard, Leah Michele; Onufrak, Stephen; Robillard, Alyssa G.; Schwartz, Randy; et al.
Practitioners in health departments, university extension programs, and nonprofit organizations working in public health face varied challenges to publishing in the peer-reviewed literature. These practitioners may lack time, support, skills, and efficacy needed for manuscript submission, which keeps them from sharing their wisdom and experience-based evidence. This exclusion can contribute to literature gaps, a failure of evidence-based practice to inform future research, reduced ability to educate partners, and delays in advancing public health practice. Our article describes the writing workshops offered to Division of Nutrition, Physical Activity, and Obesity (DNPAO), Centers for Disease Control and Prevention (CDC) funded programs in 2021. This project consisted of three 60-minute introductory writing webinars open to all recipients, followed by a Writing for Publications workshop, an 8- to 9-week virtual learning/writing intensive for selected writing team applicants. The Society for Public Health Education staff, consultants, and CDC/DNPAO staff developed, refined, and presented the curriculum. The workshop for public health practitioner writing teams was offered to two cohorts and included extensive coaching and focused on potential submission to a Health Promotion Practice supplement, "Reducing Chronic Disease through Physical Activity and Nutrition: Public Health Practice in the Field" (see Supplemental Material), which was supported by CDC/DNPAO. We describe the webinars, the workshop design, modifications, evaluation methods and results.